Interface Design Proposal of Card-Type Programming Tool - Tetsumura, Naoki; Oshima, Toru; Koyanagi, Ken’ichi; Masuta, Hiroyuki; Motoyoshi, Tatsuo; Kawakami, Hiroshi (Intelligent Robotics and Applications, 2016)
We developed a card-type programming tool “Pro-Tan” as an education tool for beginners in programming. This tool was designed to be usable without any instruction on its operations. In the experiment, we did not tell the users how to use any of the tools. The subjects were instructed to create a program by themselves. We found problems of Pro-Tan’s design in the experiment. In this paper, we report the system configuration of Pro-Tan and problem of Pro-Tan’s design.